1988
DOI: 10.1128/iai.56.8.2060-2068.1988
|View full text |Cite
|
Sign up to set email alerts
|

Clonal diversity of Neisseria meningitidis from a population of asymptomatic carriers

Abstract: Genetic diversity and relationships among 109 isolates ofNeisseria meningitidis obtained from throat cultures of healthy individuals in Norway in 1984 were assessed by analyzing electrophoretically demonstrable alielic variation at 15 enzyme-encoding chromosomal genes. Seventy-eight distinctive electrophoretic types (ETs), representing multilocus genotypes, were identified. The mean genetic diversity per locus among the 78 ETs (0.538) was equivalent to that among 19 ETs represented by 66 isolates collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(53 citation statements)
references
References 24 publications
6
46
1
Order By: Relevance
“…2.1. Bacterial strains, plasmids and growth conditions N. meningitidis strain H44/76 (B:15:P1.7,16) was originally isolated from the cerebrospinal £uid of a meningitis patient in Norway and was shown to belong to the ET-5 group of strains associated with many cases of disease [16]. Cultures of the strain were started from frozen stocks and grown overnight in Tryptic soy broth.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2.1. Bacterial strains, plasmids and growth conditions N. meningitidis strain H44/76 (B:15:P1.7,16) was originally isolated from the cerebrospinal £uid of a meningitis patient in Norway and was shown to belong to the ET-5 group of strains associated with many cases of disease [16]. Cultures of the strain were started from frozen stocks and grown overnight in Tryptic soy broth.…”
Section: Methodsmentioning
confidence: 99%
“…The genome sequences of N. meningitidis serogroup A strain Z2491 [6] and serogroup B strain MC58 [7] were searched for genes putatively encoding autotransporters by homology searching using the sequences of 28 autotransporters from 10 di¡erent bacterial species (Table 1). This list was based upon the sequences described by [16] and [10], and, additionally, TibA [17], PssA [18] and Vag8 [19] were included. Database searches were performed using the web sites of The Sanger Centre (http://www.…”
Section: Database Searchesmentioning
confidence: 99%
“…Patient strains are encapsulated and five of these serogroups (A, B, C, W135, and Y) cause more than 90% of the invasive disease worldwide (Pollard, 2004). In contrast, c. 50% of the strains isolated from carriers lack capsule and are therefore serologically not serogroupable (Caugant et al, 1988;Ala'Aldeen et al, 2000). There are two essential reasons for the lack of capsule -the deletion of the capsule locus (the capsule nul or cnl meningococci) or down-regulation of the expression of the capsule either temporarily or permanently by one of a number of genetic mechanisms (Claus et al, 2002).…”
Section: Differentiation Of Carrier Vs Patient Strains Phenotypic DImentioning
confidence: 99%
“…Comparisons of meningococci isolated from asymptomatic carriage and disease have demonstrated that meningococcal populations are genetically and antigenically highly diverse (Caugant et al, 1987a, but that a minority of genotypes and antigenic types, the 'hyperinvasive lineages', account for the majority of disease (Caugant et al, 1988;Urwin et al, 2004;Yazdankhah et al, 2004). Detailed and accurate isolate characterization is therefore a particularly important element in studies of meningococcal epidemiology, population biology and evolution.…”
Section: Introductionmentioning
confidence: 99%